Electronic and optical characterization of 2D Ti2C and Nb2C (MXene) thin films. (20th February 2019) - Halim, Joseph; Persson, Ingemar; Moon, Eun Ju; Kühne, Philipp; Darakchieva, Vanya; Persson, Per O Å; Eklund, Per; Rosen, Johanna; Barsoum, Michel W
Abstract: Two-dimensional (2D) transition metal carbides and/or nitrides (MXenes) are a new class of 2D materials, with extensive opportunities for property tailoring due to the numerous possibilities for varying chemistries and surface terminations. Here, Ti2 AlC and Nb2 AlC MAX phase epitaxial thin films were deposited on sapphire substrates by physical vapor deposition. The films were then etched in LiF/HCl solutions, yielding Li-intercalated, 2D Ti2 CT z and Nb2 CT z films, whose terminations, transport and optical properties were characterized. The former exhibits metallic conductivity, with weak localization below 50 K. In contrast, the Nb-based film exhibits an increase in resistivity with decreasing temperature from RT down to 40 K consistent with variable range hopping transport. The optical properties of both films were determined from spectroscopic ellipsometry in the 0.75 to 3.50 eV range. The results for Ti2 CT z films confirm the metallic behavior. In contrast, no evidence of metallic behavior is observed for the Nb2 CT z film. The present work therefore demonstrates that one fruitful approach to alter the electronic and optical properties of MXenes is to change the nature of the transition metal.